Pengaruh Kinerja Keuangan, Ukuran Perusahaan Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Perusahaan Food And Beverage Yang Terdaftar Di Bei Periode 2016-2018 - Salsalbila Junita Sari; Nur Hidayati; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe  purpose  of  this  research was  to  find  out  how  the Financial Performance, Firm Size And Investment Decision has an effect on the Firm Value.  Type of this Research is explanatory research. The  population  in  this  research  is  Company of  Food and Beverages listed on the Indonesia Stock Exchange (IDX) period of 2016-2018. The sample in this study  is  9 companies which  uses  purposive  sampling  technique.  The  method  of  research   is multiple linear regression analysis because this research have more than one variabel. Based on The result That Financial Performance, Firm Size And Investment Decision has an effect on the Firm Value. Financial performance has not a significant affect on Firm Value, Firm Size has a significant and negative affect on Firm Value, and Investment decision has not a significant affect on Firm Value.Keyword: Financial Performance, Firm Size, Investment And Firm Value